Quality, Acceptability and Shelf Life Study of Micronutrient Fortified Indian Traditional Sattu - D, Mridula; Jain, Rita; Singh, K K (Journal of Agricultural Engineering, 2009)
Three different fortified bengal gram and barley based sattu samples were prepared following standardized sattu making process and fortified as per FDA guidelines of flour for vitamins (thiamin, riboflavin, and niacin) and minerals (calcium and iron), packaged in low density polyethylene and laminated aluminium foil pouches and stored at 25degree C, 35degree C and room temperature. Proportion of bengal gram and barley in different sattu samples was 100:0, 50:50 and 75:25. Although some changes in alcoholic acidity and moisture content were observed during 180 days storage period in different sattu samples at all the storage conditions, but these were within the permissible limit as per BIS standard. Free fatty acids also increased at all storage conditions; however it did not affect the degree of sensory acceptability of sattu samples. Protein digestibility in fortified sattu samples with 100:0, 50:50 and 75:25 parts of bengal gram and barley was 80.58%, 76.77% and 78.62%, respectively. Fortified bengal gram sattu provided 27.68% digestible protein, 5.23% fat, 3.21% ash, 1.03% dietary fibre, 396 Kcal, 170 mg calcium, and 12.5 mg iron per 100 g. Fortified sattu samples with 50:50 and 75:25 parts of bengal gram and barley provided 19.49 and 23.58% digestible protein; 3.31 and 4.21% fat; 2.57 and 2.93% ash; 1.45 and 1.11% dietary fibre; 387 and 391 Kcal; 130.78 and 144.58 mg calcium; and 8.39 and 10.4 mg iron per 100 g, respectively. Although the overall quality of the sattu samples stored at different storage condition was within the safe and acceptable limit, but the deterioration was low in sattu samples stored at 25degree C (65%RH) in laminated aluminium foil pouches and hence may be considered for safe storage of sattu. Due to safer limit of alcoholic acidity 0.13%, overall nutritional quality, higher mean sensory score for roasted odour (7.61) and flavour and taste (8.14) of stored fortified bengal gram sattu, there is a scope for commercial production of nutritionally balanced bengal gram sattu with vitamins and minerals.